The Triumvirate NLP, NLG and NLU- Effect on AI within the purview of Computational linguistics - G K, Chithra; K, Santhi; T., Chellatamilan; Nanjangud Gopalkrishna, Nagakala; .T, Anandkrishnan (International Journal of Psychosocial Rehabilitation, 2020)
This paper is a factual breakthrough in the field of artificial intelligence AI underlying natural language processing (NLP), natural language generation (NLG), and natural language understanding (NLU) that are productively reflected in pedagogical ways of innovation in several mushroom platforms through computational linguistics on a larger scale. Natural Language Processing, Natural Language Generation, and Natural Language Understanding is a way of analyzing multi-dimensional texts by computerized means within the AI environment of computational linguistics from a broader perspective in a dynamic way. NLP involves the gathering of knowledge on “how human beings understand and use language." This is done in order to develop appropriate tools and techniques that could make computer systems understand and manipulate natural languages to perform various desired tasks. This paper reviews the literature on NLP. It also covers or gives a hint about the history of NLP. It is based on document analysis. This research paper could be beneficial to those who wish to study and learn about NLP, NLG, and NLU within the sphere of AI, under the supreme banner of computational linguistics. We can simply reach the conclusion that this triumvirate overlaps among themselves to a great extent, such as machine learning and deep learning under the label of AI through computational linguistics.